Positive psychology pioneers: Kristin Neff's power and potential to influence mental health nursing. (2nd January 2023) - Macfarlane, Jan
Abstract : This article is the fifth in a series that celebrates the work of positive psychologists and how their work has the power and potential to influence mental health nursing practice. In this article, the work of Kristin Neff and her work on self-compassion is discussed. The practical activities provided in the article will help the reader increase their own awareness of self-compassion to develop their use and transferability within their own life.